2018
DOI: 10.1111/pace.13426
|View full text |Cite
|
Sign up to set email alerts
|

Absence of late gadolinium enhancement on cardiac magnetic resonance imaging in ventricular fibrillation and nonischemic cardiomyopathy

Abstract: Most VF survivors with a diagnosis of NICM did not have LGE on CMR and would not have met primary prevention ICD criteria based on LVEF. Absence of LGE may not portend a benign prognosis in NICM. Novel strategies for determining SCD risk in this cohort are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…LGE (24) underscores the challenges further. Whether more robust phenotyping provided by ECV quantification of DMF improves risk-stratification and identifies high risk subgroups with DMF ultimately requires randomized trials of ECV-guided care to establish benefit (analogous to LGE guided-care under investigation, NCT05568069, NCT01918215).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LGE (24) underscores the challenges further. Whether more robust phenotyping provided by ECV quantification of DMF improves risk-stratification and identifies high risk subgroups with DMF ultimately requires randomized trials of ECV-guided care to establish benefit (analogous to LGE guided-care under investigation, NCT05568069, NCT01918215).…”
Section: Discussionmentioning
confidence: 99%
“…Given the observation that substantial proportions of ICD recipients never require ICD therapies, and given their costs and their risks including infection and inappropriate shock, optimal risk stratification requires further understanding, especially for primary prevention in nonischemic cardiomyopathy as exemplified by the DANISH Trial. (46) The significant proportion of SCD survivors who do not exhibit focal MF with LGE(24) underscores the challenges further. Whether more robust phenotyping provided by ECV quantification of DMF improves risk-stratification and identifies high risk subgroups with DMF ultimately requires randomized trials of ECV-guided care to establish benefit (analogous to LGE guided-care under investigation, NCT05568069, NCT01918215).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac magnetic resonance with LGE plays an important role in patients' workup by assessing for foci of myocardial fibrosis. Moreover, the presence of LGE in patients with nonischemic cardiomyopathy indicates higher mortality and morbidity rates and could indicate worse reversibility of ventricular remodeling [24][25][26][27]. A recent meta-analysis, which included 34 separate studies with a total of 5076 patients (4554 unique patients), concluded that the presence of LGE was associated with a 3.4 [95% CI: 2.04-5.67] higher risk of cardiovascular mortality, a 4.52 risk [95% CI: 3.41-5.99] of ventricular arrhythmic events, and only a 0.15 [95% CI: 0.06-0.36] higher risk of LV reverse remodeling, thus further underscoring the prognostic value of LGE in patients with DCM [23].…”
Section: Discussionmentioning
confidence: 99%
“…LGE-CMR furthermore depends on several factors such as the timing of contrast injection and selection of scan parameters that can impact the interpretation of intensity values on imaging. Another limitation of LGE for risk stratification of SCD is that a subset of patients with NICM who develop VF may not have LGE on CMR ( 50 ). Several alternative measures derived from CMR have been proposed that may address some of these limitations, including native T1 mapping and extracellular volume (ECV), which reflect diffuse fibrosis, a characteristic not captured by LGE ( 51 , 52 ).…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%